2022
DOI: 10.3390/ijerph191710974
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Toxicity and Health Effects Mechanism of Cadmium to Three Green Algae

Abstract: As algae are extremely sensitive to heavy-metal ions and can be critical biological indicators in the heavy-metal toxicity analyses conducted by environmental health researchers, this paper explores the sensitivity to temporal toxicity of three species of green algae: Scenedesmus obliquus, Chlorella pyrenoidosa, and Selenastrum capricornutum. The method of time-dependent microplate toxicity analysis was used to systematically investigate the changes in the toxicities of the three green-algae species induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Their pivotal role in diverse physiological and biochemical processes cannot be understated, encompassing photosynthesis, respiration, signal transduction, and the antioxidant system, laying a solid foundation for plant growth and metabolisms ( Moenne et al, 2016 ; Maleki et al, 2017 ). An increasing number of reports have indicated that heavy metals can restrain the growth of various algae and influence their physiological function, accompanied by the changes in photosynthetic pigments, polysaccharides, and protein ( Chen et al, 2012 ; Bosnir et al, 2013 ; Cao et al, 2015b ; Cheng et al, 2016 ; Mu et al, 2018 ; Bhattacharya, 2020 ; Nowicka et al, 2020 ; Wang et al, 2021 ; Mo et al, 2022 ). However, El Agawany et al (2021) indicated that protein content of Dunaliella tertiolecta increased under low concentrations of Ni + , Zn 2+ , and Cu 2+ , whereas high concentrations of heavy metals impeded protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Their pivotal role in diverse physiological and biochemical processes cannot be understated, encompassing photosynthesis, respiration, signal transduction, and the antioxidant system, laying a solid foundation for plant growth and metabolisms ( Moenne et al, 2016 ; Maleki et al, 2017 ). An increasing number of reports have indicated that heavy metals can restrain the growth of various algae and influence their physiological function, accompanied by the changes in photosynthetic pigments, polysaccharides, and protein ( Chen et al, 2012 ; Bosnir et al, 2013 ; Cao et al, 2015b ; Cheng et al, 2016 ; Mu et al, 2018 ; Bhattacharya, 2020 ; Nowicka et al, 2020 ; Wang et al, 2021 ; Mo et al, 2022 ). However, El Agawany et al (2021) indicated that protein content of Dunaliella tertiolecta increased under low concentrations of Ni + , Zn 2+ , and Cu 2+ , whereas high concentrations of heavy metals impeded protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of heavy metals to inhibit microalgal growth depends on the metal concentration, the specific species of algae, and the exposure time [6,7,56]. Growth reduction in response to Cd has been reported for many algal species, such as Chlorella vulgaris [56], Chlamydomonas reinhardtii [12,57], A. obliquus, Chlorella pyrenoidosa, and Selenastrum capricornutum [58]. The higher inhibition of D. armatus growth observed in our studies with increased Cd concentrations may be explained by its damaging effects on algal cell morphology and physiology [40].…”
Section: Algal Growthmentioning
confidence: 99%
“…Compared to unstressed D. armatus cells, significant increases in the contents of H 2 O 2 (by 82.6%) and MDA (by 51.9%) were observed in cultures exposed to 10 µM of Cd at 96 h of cultivation (Figure 3). Oxidative stress induced by heavy metals has been reported in many vascular plant species [12,57] and algae, such as C. vulgaris [3], A. obliquus, C. pyrenoidosa, and S. capricornutum [58]. Consequently, Cd disrupts the redox homeostasis, thereby affecting the cell functioning and tolerance potential of alga D. armatus.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…In addition, the massive production of these reactive oxygen species could trigger or intensify the membrane lipid peroxidation, causing serious damage to the membrane system. The product of the membrane lipid peroxidation, MDA, could be used as an indicator to reflect the oxidative pressure faced by algae cells [45]. As seen in Figure 5, MDA content was insignificantly different at 1-7.…”
Section: Antioxidant Enzyme Activities and Mda Content Analysismentioning
confidence: 99%